Elderly Medication and Safety (EMAS) education program / Mohd Shahezwan Abd Wahab … [et al.] - Abd Wahab, Mohd Shahezwan; Ali, Aida Azlina; Halim, Hasseri; A. Wahab, Izyan (Research Innovation Business Unit, 2014)
The chronological age of 65 years and above has been accepted as a definition of elderly or older person. Worldwide, elderly population has been increasing over the years due to medical technologies advancement, improved health promotion and services. In Malaysia the number of those categorised as elderly population was approximately 1.5 million in the year 2000 and this number is expected to increase to 3 million in 2020. The elderly are frequent users of medications and health services since they generally co-exist with multiple co-morbidities. Due to age related-physiological changes that affect the pharmacokinetics and pharmacodynamics of medications, the elderly are prone to developing drug-related problems (DRPs) and adverse drug reactions (ADRs). Optimizing medication use among the elderly is challenging due to multiple medication use, reduced physical and mental functioning and low level of medication compliance. At present there is no therapeutic educational program focusing on the elderly that interconnects physicians, pharmacists and the elderly. Therefore the implementation of EMAS project could fill the gap in promoting better care for the geriatrics. EMAS project is aimed to improve medication use in the elderly through its various programs. The project consists of three components: education, research and community services. In the educational part of the project, educational materials on geriatric medications will be sent to physicians, hospital and community pharmacists and elderly care institutions to provide common geriatricrelated information such as medication pharmacokinetics and pharmacodynamics changes, physiological changes, potentially inappropriate medications/ potentially prescribing omissions and common geriatric syndromes in the elderly. A group of clinical experts will contribute to the development of the educational materials which was specifically developed for the elderly and healthcare professionals who are involved in geriatric care. Medical conditions that are common in the elderly such as heart failure, diabetes, falls and gout will be covered more extensively in the educational program. As part of EMAS, continuing professional development (CPD) program in the form of lecture, talk or forum will also be organized for the healthcare professionals to provide latest updates and information on geriatrics pharmacotherapy. A CPD program website will also be developed for healthcare professionals who could provide comprehensive and good quality online training support for the pharmacists and doctors in the area of geriatrics. This website will be the first in the country to compile reliable information regarding elderly medication for easy reference. For the laypeople, series of talks on optimization of geriatric medication use will be held regularly. This would provide opportunities especially the elderly to better understand the importance of optimal medication use among them. EMAS project would also provide series of community services in which basic health screening is offered to the elderly at the elderly care institutions in collaboration with governmental and non-governmental organization. Health screening services that could be provided includes blood pressure, body mass index (BMI), glucose, total cholesterol and nutrition awareness. Through this health screening program, those who may be at risk for certain illnesses may be identified. EMAS project can be seen as an ongoing commitment designed specifically to improve health and medication use in the elderly. Since the program involves the participation of academicians, healthcare professionals and the elderly themselves, EMAS offers a holistic approach in optimizing medication use for the elderly